Acute liver failure secondary to hepatic infiltration: a single centre experience of 18 cases. Issue 4 (1st April 1998) - Rowbotham, D; Wendon, J; Williams, R
Abstract : Background —Acute liver failure (ALF) secondary to malignant infiltration of the liver is rare and is diagnosed often only after death. Aims —To determine diagnostic factors and particular clinical patterns of illness. Methods —Review of case notes from all patients with ALF secondary to hepatic infiltration admitted to this unit over an 18 year period (1978–1995). Results —From a total of 4020 admissions, 18 patients were identified with ALF attributable to hepatic infiltration. Mean age was 40.7 years. Aetiology was non-Hodgkin's lymphoma in nine patients, Hodgkin's disease in three, infiltrative metastatic carcinoma in four, and haemophagocytosis with no precipitant cause in two cases. Prodromal symptoms were non-specific, but occurred at least two to four weeks before onset of ALF, making the presence of such symptoms of value in differential diagnosis of the cause of ALF. Clinical examination and investigations were unhelpful in distinguishing these cases from more usual causes of ALF. Usually, the clinical course was of rapid deterioration and death from multiorgan failure, and only one patient survived. Diagnosis was made during life in 15 patients. Histology showed evidence of widespread hepatocellular necrosis, with diffuse infiltration by tumour cells rather than focal cellular aggregation. Conclusions —Only with accurate histological diagnosis from liver biopsy and institution of specific therapy early in the management of such patients will the best chance of recovery be achieved. In every case of ALF with prodromal symptoms or abnormal imaging, hepatic histology should be obtained by liver biopsy as soon as possible to diagnose infiltrative hepatic disease.